Tumor Cell-Induced Platelet Aggregation as an Emerging Therapeutic Target for Cancer Therapy - Strasenburg, Wiktoria; Jóźwicki, Jakub; Durślewicz, Justyna; Kuffel, Błażej; Kulczyk, Martyna Parol; Kowalewski, Adam; Grzanka, Dariusz; Drewa, Tomasz; Adamowicz, Jan (Frontiers in Oncology, 2022)
Tumor cell shave the ability to induce platelet activation and aggregation. This has been documented to be involved in tumor progression in several types of cancers, such as lung, colon, breast, pancreatic, ovarian and brain cancer. During the process, platelets protect circulating tumor cells from the deleterious effects of shear forces, shield tumor cells from the immune system and provide growth factors, facilitating metastatic spread and tumor grow that the original site as well as at the site of metastasis. Here in we present a wider view on the induction of platelet aggregation by specific factors primarily developed by cancer, including coagulation factors, adhesion receptors, growth factors, cysteine proteases, matrix metalloproteinases, glycoproteins, soluble mediators and selectins. These factors may be presented on the surface of tumor cells as well as in its microenvironment and some may trigger more than just one simple receptor-ligand mechanism. For a better understanding we briefly discuss the physiological role of the factors in the platelet activation process and subsequently we provide scientific evidence and discuss their potential role in progression of specific cancers. Targeting TCIPA (Tumor Cells Induced Platelet Aggregation) by anti-platelet drugs may open ways to develop new treatment modalities. On the one hand, it may affect patients’ prognosis by enhancing known therapies in advanced-stage tumors. On the other hand, the use of drugs that are mostly easily accessible and well-known for their pharmacokinetics and side effects, may be an opportunity to propose an unparalleled anti-tumor prophylaxis. In this review we present recent discoveries of mechanisms by which cancer cells activate platelets and discuss new platelet-targeted therapeutic strategies.